2005
DOI: 10.1021/la0520334
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Transitions in Nonionic Surfactant Adsorbed Layers near Their Cloud Points

Abstract: The structure of adsorbed layers of several polyoxyethylene alkyl ether (C(n)E(m)) nonionic surfactants on silica and graphite surfaces has been imaged using atomic force microscopy as a function of temperature up to their cloud points. For all surfactants with a cloud point within the experimentally accessible range, the adsorbed layer morphology on silica evolved from globules at low temperatures first into rods and then a mesh with increasing temperature. This mesh structure was retained even when the solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…The transition of morphology during the clouding of several polyoxyethylene alkyl ether (CnEm) nonionic surfactants with CP ≤ 40°C, was studied from Fourier transform atomic force microscopic images of adsorbed layers of aqueous solution of those surfactants on silica and graphite surfaces at temperatures below and near CP [194]. The adsorption morphology of the surfactants changes from initial globules to rod with the rise in temperature and finally to a mesh structure near cloud point.…”
Section: Morphological Study Of Cloudingmentioning
confidence: 99%
“…The transition of morphology during the clouding of several polyoxyethylene alkyl ether (CnEm) nonionic surfactants with CP ≤ 40°C, was studied from Fourier transform atomic force microscopic images of adsorbed layers of aqueous solution of those surfactants on silica and graphite surfaces at temperatures below and near CP [194]. The adsorption morphology of the surfactants changes from initial globules to rod with the rise in temperature and finally to a mesh structure near cloud point.…”
Section: Morphological Study Of Cloudingmentioning
confidence: 99%
“…3 might be that the film morphology changes from rods to globules, and then a bilayer with increasing MEDDAB content, as a mesh structure does not look dissimilar to an adsorbed layer of globular aggregates under the AFM. However this progression is unlikely as the film would have to first increase in curvature and then change to a planar conformation with further addition of MEDDAB [24,25]. Another means of distinguishing a deflection image of globules from that of a mesh is that the periodicity of the mesh is usually larger [24].…”
Section: Dtab and Meddab Mixed Filmsmentioning
confidence: 99%
“…A wealth of AFM studies of surfactant self-assembly on various substrates have revealed the existence of globular [20], cylindrical [16,17], mesh [24,25] and bilayer [17,26] structures. The effects of factors such as alkyl chain length [15], headgroup structure and charge [18,20], counterion type [20] and electrolyte concentration [27,28] all been found to mirror the structural trends observed in bulk self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Among these non-ionic surfactants, polyethoxylated alkyl ones (C n E m , where n is the number of carbons of the hydrophobic and saturated linear chain, and m is the number of ethoxy groups in the polar head) [12] are one of the most useful surface-active substances, attracting the interest of the scientific community, due to their remarkable and unique properties [13][14][15]. In the oil industry, they have been used in metalworking fluids [16], drilling fluid formulations [17] as well as systems with biocide activity [18].…”
Section: Introductionmentioning
confidence: 99%